HERITABILITAS DAN KORELASI GENOTIPIK ANTARA KARAKTER KUANTITATIF DENGAN HASIL BEBERAPA GALUR PADI BERAS HITAM M4 HASIL INDUKSI MUTASI - Suliartini, Ni Wayan Sri; Sudika, I Wayan; Maisopa, Ira; Aryana, I Gusti Putu Muliarta; Sudharmawan, Anak Agung Ketut; Ambarwati, Zaskia Putri; Azhari, Anjar Pranggawan (Fakultas Pertanian Universitas Mataram, 2024)
This research aims to determine the heritability value in the broad sense of several quantitative traits of black rice lines and to determine the correlation coefficient value between quantitative traits and the yield of black rice rice resulting from mutation induction. This research was carried out from March to August 2023 in Saribaye Village, Lingsar District, West Lombok Regency, West Nusa Tenggara. This research used a Randomized Block Design (RAK) consisting of 25 treatments with 3 replications, namely 15 Baas Selem mutants and 10 G10 strains. Observation data were analyzed using analysis of variance with a level of 5%. The research results show that the heritability value is one trait in the high category, namely plant height, while four traits have medium heritability values, namely panicle length, number of filled grains per panicle, number of empty grains per panicle, weight of 100 grains, and weight of filled grains per hill, as well as three Traits with low heritability are the number of productive offspring, the number of non-productive offspring, and the total number of offspring. Quantitative traits had a positive genotypic correlation with yield, namely plant height, number of productive tillers, panicle length and weight of 100 grains, while the total number of tillers had a negative genotypic correlation.